Evaluation of crop and pond-deepening adaptations to climate change in saline coastal Bangladesh: Benefit-cost and risk analysis - Md. Jahangir Kabir; Donald S. Gaydon; Rob Cramb (Agricultural Water Management)
This study estimates the irrigation water requirement and irrigation water productivity (IWP) of dry-season crops across various sowing dates, and assesses the economic viability of different potential adaptation options. Our findings indicate that current farming practices require 25–48 % more irrigation water for non-rice grain crops, while optimal approaches and government recommendations (BARI/BRRI) lead to more efficient water utilization. IWP of potential DS crops following optimum sowing increased by 89–433 % under the current conditions and by 28–158 % under future conditions, compared to farmers’ practices. Notably, achieving a higher grain yield per hectare does not always correspond to higher economic returns from the limited freshwater supply across crops. Our cost-benefit analysis (BCA) reveals a positive net present value (NPV, ranging from BDT 23,750–91,167) and favourable cost-benefit ratios (BCR > 1, ranging from 2.4 to 5.6 BDT over a seven-year period) for investments in deepening home-yard ponds for aquaculture and dry-season cropping across various sowing and transplanting options across farm types. Risk analysis results have confirmed that in the 80th percentile, every BDT spent on pond deepening for aquaculture and rice and non-rice dry-season crop cultivation returns between 2.8 and 9.8 BDT across farm types. We recommend diversifying crops using the optimal sowing/transplanting options, alongside enhancing on-farm water storage since the optimal sowing option efficiently uses scarce freshwater and consistently performs better, and as a result, it has a more suitable window for sowing crops in saline coastal soil. This approach ensures increased farm income and mitigates risks associated with environmental stress challenges.